Bioactivity‐directed isolation, characterization, and quantification of an anxiolytic flavonoid from Brassica oleracea L. Issue 4 (4th March 2021) - Kaur, Divneet; Shri, Richa; Kamboj, Anjoo
Abstract: Brassica oleracea L. or Broccoli, is known for its numerous health benefits attributed to the rich array of phytochemicals. Our earlier study showed the hydroalcoholic extract of Broccoli had significant antianxiety activity. The present study involved bioactivity‐directed fractionation of the active extract with the aim of separating the constituent responsible for the activity. The bioactive extract was fractionated by column chromatography. The antianxiety activity of the obtained fractions and sub‐fractions was evaluated using the elevated plus maze model in mice. It led to the isolation of the bioactive compound. The antianxiety effect was confirmed by hole‐board test and mirror chamber test. Structure of the compound was characterized by UV, IR, 1 H NMR, 13 C NMR, MS techniques, and was found to be kaempferol‐3‐O‐β‐D‐glucoside. The content of kaempferol‐3‐O‐β‐D‐glucoside in florets of B. oleracea was determined by HPTLC. It was found to be present to the extent of 0.061% w/w. Practical applications: Anxiety disorders cause immense suffering worldwide and hence search for safe and effective antianxiety drugs has become important area of research. Most commonly and widely prescribed drugs for anxiety that is, benzodiazepines may cause many adverse effects such as drowsiness, confusion, dizziness etc. They also cause physical dependence and withdrawal symptoms. Flavonoids, and their semi‐synthetic derivatives, moreover, do not cause any such side effects unlike benzodiazepines. Broccoli or Brassica oleracea is reported to contain a number of flavonoids like quercetin, kaempferol, and their derivatives. In the present investigation, bioactivity‐guided isolation showed that the antianxiety activity of B. oleracea is due to kaempferol‐3‐O‐β‐D‐glucoside, a compound which has been earlier reported to be present in B. oleracea . Hence, after detailed investigation this compound can be developed into a potential antianxiety drug. Abstract : The present study involved bioactivity‐directed fractionation of the active extract with the aim of separating the constituent responsible for the activity. Bioactivity‐guided fractionation of B. oleracea ultimately led to the isolation of kaempferol‐3‐O‐β‐D‐glucoside which is responsible for its antianxiety activity. Kaempferol‐3‐O‐β‐D‐glucoside has marked antianxiety promise and may be developed into a safe anxiolytic drug.